1978
DOI: 10.1111/j.1365-3083.1978.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Many Bacterial Species are Mitogenic for Human Blood B Lymphocytes

Abstract: Thirty bacterial species were tested for their ability to stimulate to increased DNA synthesis in human blood lymphocytes. A definite stimulation was obtained with eighteen bacterial species. For three of these species ten different strains of each were tested, and all increased DNA synthesis. The maximum response was after 3--4 days of culture, suggesting a mitogenic effect. This was confirmed by the induction of polyclonal antibody production shown by a plague assay, which was positive for nine of eleven spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The mitogenic activity of staphylococcal cells was previously thought to be due to the presence of protein A, as protein A-rich strains possessed high mitogenic activity, whereas strains containing no protein A were very weakly or not mitogenic [16,31] [31] with whole staphylococ cal cells was much greater than that pro duced by isolated soluble or Sepharosebound protein A. These results suggested that some other components of staphylococ ci could also possess mitogenic activity, but these authors could not detect any mitogenicity of staphylococcal PG and TA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitogenic activity of staphylococcal cells was previously thought to be due to the presence of protein A, as protein A-rich strains possessed high mitogenic activity, whereas strains containing no protein A were very weakly or not mitogenic [16,31] [31] with whole staphylococ cal cells was much greater than that pro duced by isolated soluble or Sepharosebound protein A. These results suggested that some other components of staphylococ ci could also possess mitogenic activity, but these authors could not detect any mitogenicity of staphylococcal PG and TA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of products from various bacteria has been shown to possess mitogenic activity, includ ing lipopolysaccharides (LPS) from gram negative bacteria [reviewed in 3], PPD tu berculin from Mycobacterium tuberculosis [10], acidic polysaccharide from Serratia piscatorum [11], Listeria monocytogenes cell walls [12], streptococcal extracellular products [13], and others. Also, cells of a number of microbial species have been shown to be mitogenic, including Coryne-bacterium parvum [14], Mycoplasma pneu moniae [15], Staphylococcus aureus, Hae mophilus influenzae, Bordetella pertussis, M. tuberculosis, Neisseria catarrhalis, Neis seria gonorrhoeae, Neisseria pharyngis, Ba cillus, Streptococcus pneumoniae, Strepto coccus pyogenes, and Streptococcus group G [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Fab part is then degraded, whereas the Fc fragment is endocytosed together with the Ag. M. catarrhalis selectively binds the IgD BCR, and proliferation of human B lymphocytes follows its interaction with cell surface IgD and MHC class I molecules (17)(18)(19). In the present study, we showed that MID bound all surface-expressed IgD BCRs on B lymphocytes isolated from human peripheral blood (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, H. influenzae has the capacity to reside in tonsils (25), where the IgD binding phenotype could allow for interaction with the human BCR. In fact, a mitogenic effect of Hib on human B cells has been reported (26). This effect might parallel the one M. catarrhalis has on human PBLs (27,28) and possibly serve to increase the virulence of Hib.…”
Section: Discussionmentioning
confidence: 96%